Pore-Network Modeling of Water and Vapor Transport in the Micro Porous Layer and Gas Diffusion Layer of a Polymer Electrolyte Fuel Cell - Chao-Zhong Qin (Computation, 2016)
In the cathode side of a polymer electrolyte fuel cell (PEFC), a micro porous layer (MPL) added between the catalyst layer (CL) and the gas diffusion layer (GDL) plays an important role in water management. In this work, by using both quasi-static and dynamic pore-network models, water and vapor transport in the MPL and GDL has been investigated. We illustrated how the MPL improved water management in the cathode. Furthermore, it was found that dynamic liquid water transport in the GDL was very sensitive to the built-up thermal gradient along the through-plane direction. Thus, we may control water vapor condensation only along GDL-land interfaces by properly adjusting the GDL thermal conductivity. Our numerical results can provide guidelines for optimizing GDL pore structures for good water management.